Genome sequence and description of Clostridium niameyense sp. nov., isolated from a human with marasmus in Nigeria. (July 2018) - Chabou, S.; Tidjani Alou, M.; Khelaifia, S.; Lagier, J.-C.; Labas, N.; Cimmino, T.; Diene, S.; Raoult, D.; Rolain, J.-M.
Abstract: Clostridium niameyense sp. nov. strain MT5 is the type strain of C. niameyense sp. nov., a new species within the genus Clostridia. C. niameyense is a Gram-positive, anaerobic bacillus. The strain MT5 (= CSUR P1468 = DSMZ 100441), whose genome is described here, was isolated from a faecal sample collected from a patient with anorexia and marasmus living in Nigeria. The genome is 2 542 841 bp long with 27.44% G + C content and consists of six scaffolds.